A biomarker of anxiety in children and adolescents: A review focusing on the error-related negativity (ERN) and anxiety across development. (October 2017) - Meyer, Alexandria
Abstract: Background: Anxiety disorders are the most common form of psychopathology and often begin early in development. Therefore, there is interest in identifying neural biomarkers that characterize pathways leading to anxiety disorders early in the course of development. A substantial amount of work focuses on the error-related negativity (ERN) as a biomarker of anxiety. While two previous reviews have focused on the relationship of the ERN and anxiety in adults, no previous review has focused on this issue in children and adolescents. Results and conclusions: Overall, 22 studies were included in the current review. A number of patterns emerged, including: 1.) The ERN is enhanced in clinically anxious children at all ages (6–18 years old), regardless of the task used to measure the ERN. 2.) Studies focusing on anxiety symptoms and temperamental fear suggest that the relationship between the ERN and normative anxiety may change across development. 3.) The ERN can predict the onset of anxiety disorders across different developmental periods. 4.) The ERN relates to other markers of risk for anxiety (e.g., aversive startle potentiation) in children and adolescents.